The Study on Marshall Design Parameter of Hot Mix Asphalt Mixture (HMA) Using Limestone Aggregate - Abdul Hamid, Muhammad Hazim; Mohd Suffi, Hairee Daniel; Yusoff, Nurul Aini Najwa; Hazirah Bujang, (Multidisciplinary Applied Research and Innovation, 2024)
In Malaysia, 80% of its roads are from flexible pavement rather than rigid pavement. The asphalt binder material is supplied by the quarry for its aggregates and from the manufacturer for its asphalt binder. In order, material such as limestone aggregate has been used to replace the material that commonly used in the mixture. Limestone aggregate is actually one of the most durable of all natural building materials. The main objective of this study is to overcome the weakness of the strength problem by using the method Marshall Stability Test. The material that was used for aggregate were limestone and granite. The properties for aggregate tested were Sieve Analysis, Aggregate Impact Value (AIV), Flakiness and Elongation. Furthermore, asphalt binder grade 60/70 penetration properties were performed by softening point and penetration testing. Next, the method used was a mixture design by Hot Mix Asphalt (HMA) and Marshall Mix design. Marshall stability test were employed to evaluated the performance of asphalt mixture. At 0, 25, 50, 70, and 100% of the aggregate total weight, the limestone was mixed with asphalt binder grade 60/70 penetration. The stiffness was demonstrate that the control sample is 74.481 kN/mm meanwhile, the optimal limestone mixture was obtained at 25% which is 69.664 kN/mm. The compressive test shown that all the sample are required followed the JKR specification for stiffness which is 2.6 kN/mm. Therefore, potential of limestone aggregate in asphalt mixture has been implement in road construction.